Cześć!
Postać ogólna funkcji kwadratowej
[tex]y=ax^2+bx+c[/tex]
1)
[tex]y=-3(x+5)(x-2)\\\\y=-3(x\cdot x-x\cdot2+5\cdot x-5\cdot2)\\\\y=-3(x^2-2x+5x-10)\\\\y=-3(x^2+3x-10)\\\\y=-3\cdot x^2-3\cdot3x-3\cdot(-10)\\\\\huge\boxed{y=-3x^2-9x+30}[/tex]
2)
[tex]y=\frac{3}{4}(x-4)^2+\frac{3}{5}\\\\y=\frac{3}{4}(x^2-2\cdot x\cdot4+4^2)+\frac{3}{5}\\\\y=\frac{3}{4}(x^2-8x+16)+\frac{3}{5}\\\\y=\frac{3}{4}\cdot x^2-\frac{3}{4}\cdot8x+\frac{3}{4}\cdot16+\frac{3}{5}\\\\y=\frac{3}{4}x^2-3\cdot2x+3\cdot4+\frac{3}{5}\\\\y=\frac{3}{4}x^2-6x+12+\frac{3}{5}\\\\\huge\boxed{y=\frac{3}{4}x^2-6x+12\frac{3}{5}}[/tex]